Science literacy center: teacher planner. (New York : Scholastic Inc., 1999)
This guide helps you organize and implement an effective science curriculum.
SET A: Insects and spiders--Animal Homes--Polar Regions--Amazon Rainforest--Weather--Trees.
Keywords: Science -- Study and teaching; Science -- Juvenile literature